The Role of Gender in Language Communication: A Short Overview - Brzozowska, Dorota (Investigationes Linguisticae, 2002)
The paper deals with the development of the gender concept and the way it is moving away from the notions of binary thinking. Its influence on the methods of linguistic analysis is taken into consideration. Different feminist ideologies – liberal, radical, socialist and cultural feminism as well as the feminism of power – are presented in the context of their view on women-men relations. Other ideologies that shape the idea of ‘doing gender’ are shown, too. All of them – postmodernism, identity politics and the globalization trend - come from outside linguistics. The binary classification is usually made automatically as an obvious and natural one. It is done against a strong tendency to underline the fuzziness of male-female boundaries in the philosophical speculations that are a starting point for the research in many disciplines.